Prevalence and Associated Factors of optrA-Positive-Enterococcus faecalis in Different Reservoirs around Farms in Vietnam - Hoang Thi An Ha; Phuong Thi Lan Nguyen; Tran Thi Mai Hung; Le Anh Tuan; Bui Thanh Thuy; Tran Hoang My Lien; Pham Duy Thai; Nguyen Ha Thanh; Vu Thi Ngoc Bich; Tran Hai Anh; Ngo Thi Hong Hanh; Nguyen Thi Minh; et al. (MDPI AG, 2023)
Linezolid is an antibiotic of last resort for the treatment of infections caused by Gram-positive bacteria, including vancomycin-resistant enterococci. Enterococcus faecalis, a member of enterococci, is a significant pathogen in nosocomial infections. E. faecalis resistance to linezolid is frequently related to the presence of optrA, which is often co-carried with fex, phenicol exporter genes, and erm genes encoding macrolide resistance. Therefore, the common use of antibiotics in veterinary might promote the occurrence of optrA in livestock settings. This is a cross-sectional study aiming to investigate the prevalence of optrA positive E. faecalis (OPEfs) in 6 reservoirs in farms in Ha Nam province, Vietnam, and its associated factors and to explore genetic relationships of OPEfs isolates. Among 639 collected samples, the prevalence of OPEfs was highest in flies, 46.8% (51/109), followed by chickens 37.3% (72/193), dogs 33.3% (17/51), humans 18.7% (26/139), wastewater 16.4% (11/67) and pigs 11.3%, (14/80). The total feeding area and total livestock unit of the farm were associated with the presence of OPEfs in chickens, flies, and wastewater. Among 186 OPEfs strains, 86% were resistant to linezolid. The presence of optrA was also related to the resistant phenotype against linezolid and levofloxacin of E. faecalis isolates. Close genotypic relationships identified by Pulsed Field Gel Electrophoresis between OPEfs isolates recovered from flies and other reservoirs including chickens, pigs, dogs, and wastewater suggested the role of flies in the transmission of antibiotic-resistant pathogens. These results provided warnings of linezolid resistance although it is not used in livestock.